TOWARDS THE DEFINITION OF THE CONCEPT OF ADMINISTRATIVE- LEGAL ACTIONS AGAINST OFFENSES IN THE SPHERE OF TAXATION IN UKRAINE (Bulletin of criminological association of Ukraine, 2025)
The article devoted to the importance of combating tax offenses, since not only the filling of state and local budgets, financing of defense, social, educational, medical, cultural spheres, infrastructure projects, as well as economic growth and quality of life of citizens depend on this. In real law enforcement conditions, a whole range of tax offenses arise that require an appropriate response from the state, in particular through mechanisms of administrative and legal counteraction. The author defines the key features of any offense as: 1) social danger or harm; 2) action as a form of manifestation; 3) illegality; 4) conscious and volitional nature. At the same time, the content of offenses in the field of taxation, in addition to the above features, is also characterized by a number of other features that are determined by the peculiarities of financial legal relations. The author emphasizes that offenses in the field of taxation have not only an economic, but also a social and legal nature. They undermine the authority of state institutions, violate the principles of justice and equality, create unequal conditions for business entities, and provoke a general decline in legal culture. Administrative and legal counteraction in the field of taxation plays a key role in ensuring the proper level of tax discipline. It allows the state to effectively counteract tax offenses without resorting to excessively repressive or slow mechanisms, maintaining a balance between ensuring budget revenues and respecting the rights of taxpayers. In the author's opinion, administrative and legal counteraction to offenses in the field of taxation in Ukraine should be considered as a set of organizational and legal measures implemented by authorized state bodies in order to identify, prevent, stop, and legally respond to facts of violation of tax legislation, by applying administrative influence measures aimed at ensuring tax discipline, protecting public interests, and restoring the violated financial and legal order.
Keywords: offense; tax offense; taxation system; administrative and legal countermeasures